2013
DOI: 10.4269/ajtmh.13-0321
|View full text |Cite
|
Sign up to set email alerts
|

The Complex Relationship between Weather and Dengue Virus Transmission in Thailand

Abstract: Using a novel analytical approach, weather dynamics and seasonal dengue virus transmission cycles were profiled for each Thailand province, 1983–2001, using monthly assessments of cases, temperature, humidity, and rainfall. We observed systematic differences in the structure of seasonal transmission cycles of different magnitude, the role of weather in regulating seasonal cycles, necessary versus optimal transmission “weather-space,” basis of large epidemics, and predictive indicators that estimate risk. Large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(123 citation statements)
references
References 37 publications
4
118
1
Order By: Relevance
“…The long-term patterns of dengue incidence have been studied at numerous endemic sites, especially in Southeast Asia [5][12] and the Americas [8], [13][15]. Results highlight intra-annual (seasonal) and inter-annual (across multiple years) signatures in transmission intensity [8], [10], [16], [17], as well as occasional abrupt shifts in the age of people with clinically apparent illness [18]. Conclusions from these studies are mixed, although in aggregate they highlight that dengue occurs across a diverse array of conditions and that the key drivers of transmission similarly vary across those different contexts [8], [10], [16].…”
Section: Introductionmentioning
confidence: 99%
“…The long-term patterns of dengue incidence have been studied at numerous endemic sites, especially in Southeast Asia [5][12] and the Americas [8], [13][15]. Results highlight intra-annual (seasonal) and inter-annual (across multiple years) signatures in transmission intensity [8], [10], [16], [17], as well as occasional abrupt shifts in the age of people with clinically apparent illness [18]. Conclusions from these studies are mixed, although in aggregate they highlight that dengue occurs across a diverse array of conditions and that the key drivers of transmission similarly vary across those different contexts [8], [10], [16].…”
Section: Introductionmentioning
confidence: 99%
“…ENSO has been identified as a potential driver of dengue in Thailand, via its impact on local climate conditions (Cazelles et al, 2005). Campbell et al, (2013) demonstrated the complexity of the association between local climatic variables and dengue dynamics in Thailand with temperature found to define a viable range for dengue transmission (with 80% of severe dengue cases occurring when mean temperature was 27-29.5°C) while humidity amplifies the potential within that range.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, seasonal dengue outbreaks may be limited by dengue’s long serial interval (perhaps 20 days [25]) and the limited time during which rainfall, high humidity, and high temperatures are optimal for the breeding of its primary vector, Aedes aegypti , and the rapid incubation of the virus [16, 29, 20]. Dengue season may last for up to 6 months in some regions, but the period of highest transmissibility is likely shorter and curtailed by the reduction in temperature and humidity by the end of each rainy season [4], so we conservatively assume that high dengue transmission occurs in a 3-month window (Figure 2b). If dengue epidemics are greatly curtailed by the short season, then the optimal vaccination coverage could be well below the critical vaccination threshold, though higher-than-optimal levels of coverage could still be cost-effective.…”
Section: Resultsmentioning
confidence: 99%